2021
DOI: 10.1242/dev.196121
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of hunchback translation in real-time and at single-mRNA resolution in the Drosophila embryo

Abstract: The Hunchback (Hb) transcription factor is critical for anterior-posterior patterning of the Drosophila embryo. Despite the maternal hb mRNA acting as a paradigm for translational regulation, due to its repression in the posterior of the embryo, little is known about the translatability of zygotically transcribed hb mRNAs. Here we adapt the SunTag system, developed for imaging translation at single mRNA resolution in tissue culture cells, to the Drosophila embryo to study the translation dynamics of zygotic hb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 62 publications
2
45
0
Order By: Relevance
“…Recently, it was demonstrated that the translation efficiency of ribosomes of the early Drosophila egg is not linear along the A-P axis, exemplified by an analysis on the gap gene hunchback ( hb ) [ 67 ]. A completely new hallmark of this report was that hb expression levels would not only be dependent on the binding of the necessary transcription factors driving the gene, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was demonstrated that the translation efficiency of ribosomes of the early Drosophila egg is not linear along the A-P axis, exemplified by an analysis on the gap gene hunchback ( hb ) [ 67 ]. A completely new hallmark of this report was that hb expression levels would not only be dependent on the binding of the necessary transcription factors driving the gene, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Introduction of the SunTag array into the protein of interest (POI), and subsequent binding of a single chain antibody-fluorescent protein fusion (scFv-FP) to the nascent SunTag peptides ( Figure 1 A), allows translation to be visualized in the Drosophila embryo ( Dufourt et al., 2021 ; Vinter et al., 2021 ). Insertion of SunTag at the start of the coding sequence enables rapid visualization of translation sites and maximizes their signal, facilitating early detection and quantitation.…”
Section: Before You Beginmentioning
confidence: 99%
“…Single molecule fluorescent in situ hybridization (smFISH) is used with SunTag labeling ( Figure 1 B) to visualize translation of individual mRNAs in fixed embryos, whereas the MS2/MCP system for mRNA detection is exploited for live imaging of translation. Insertion of 128 MS2 copies gives the required sensitivity for single mRNA detection ( Vinter et al. 2021 ; Dufourt et al.…”
Section: Before You Beginmentioning
confidence: 99%
See 2 more Smart Citations